Using Anchor Texts with Their Hyperlink Structure for Web Search - Dou, Zhicheng; Song, Ruihua; Wen, Ji-Rong (Proceedings of the 32nd Annual ACM SIGIR Conference (Sigir '09), 2009)
As a good complement to page content, anchor texts have been extensively used, and proven to be useful, in commercial search engines. However, anchor texts have been assumed to be independent, whether they come from the same Web site or not. Intuitively, an anchor text from unrelated Web sites should be considered as stronger evidence than that from the same site. This paper proposes two new methods to take into account the possible relationships between anchor texts. We consider two relationships in this paper: links from the same site and links from related sites. The importance assigned to the anchor texts in these two situations is discounted. Experimental results show that these two new models outperform the baseline model which assumes independence between hyperlinks.